Pengaruh Kurs, Suku Bunga SBI, dan Jumlah Uang Beredar Terhadap Tingkat Inflasi di Indonesia - Sarah Fitria Harahap (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Inflation, which is a monetary phenomenon that often occurs in all countries in the world, can be explained as a continuous process of rising prices. This is the main indicator in the economy and changes in the inflation rate are continuously monitored to keep it stable and low. The purpose of this study is to identify the effect of the exchange rate (exchange rate), SBI interest rates, and the money supply on the inflation rate in Indonesia. The results of the study show that simultaneously, these three factors have an influence on inflation in Indonesia. The results of the analysis show that the F value is 53.731 with a significance level of 0.000, which indicates a statistically significant effect. In addition, the value of Adjusted R square = 0.668 indicates that 66.8 percent of fluctuations in the reduction in the inflation rate in Indonesia can be explained by the exchange rate, SBI interest rates, and money supply variables included in this study. The remaining part, which is equal to 33.2 percent, is influenced by other factors that are not included in this research model.